Integration of LQR and LQT Optimal Control Technologies in DC Motors for Energy Empowerment of Maritime Communities Using Simulink Matlab - Ivan Nanda Septiandi (Politeknik Perkapalan Negeri Surabaya, 2024)
The rapid advancement of technology has significantly influenced various aspects of human life, including the field of electrical systems and control technologies. Access to information and knowledge has become increasingly seamless, fostering innovation and the development of sustainable solutions for future challenges. One critical aspect of technological advancement lies in control systems, which play a pivotal role in modern applications such as ship steering systems, aviation, and industrial automation. Control systems are essential in enhancing product performance and efficiency, especially in optimizing the operation of DC motors. A DC motor, which converts electrical energy into kinetic energy, requires precise control mechanisms to achieve optimal performance. This study focuses on the optimization of DC motors using Linear Quadratic Regulator (LQR) and Linear Quadratic Tracker (LQT) methods. By simulating these control techniques in MATLAB Simulink, this paper evaluates the performance of DC motors under the influence of added noise. The results aim to demonstrate how these advanced control strategies can improve energy efficiency and system stability. Furthermore, the research highlights the practical application of this technology to empower maritime communities by addressing energy challenges, promoting sustainability, and supporting community-based technological adoption.